ANALYSIS OF THE MOVIE DATABASE FILM RATING PREDICTION WITH ENSEMBLE LEARNING USING RANDOM FOREST REGRESSION METHOD - Marpid, Nuravifah Novembriana; Kurniawan, Yogiek Indra; Rahayu, Swahesti Puspita (Informatika, Universitas Jenderal Soedirman, 2025)
The film industry has become a very profitable industry. However, during COVID-19 the film industry experienced an unfavorable impact with the delay in the screening schedule of new films, many cinemas were prohibited from operating so they were completely closed, and it wasn’t easy to obtain permits to carry out the filmmaking process. To survive in this industry from the impact of the pandemic, it is necessary to consider several factors such as targeted promotion methods by using the right selection of predictive decisions with market and trends. Predicting the success of a film is very helpful in determining the success rating and quality of the film to be released. The Random Forest Regression method is used to conduct predictive analysis on films. This study uses the M-estimate encoding technique to handle categorical data into numerical data, and the result shows that the application of M-estimate encoding increases the correlation value between features. In the Random Forest Regression method with 1000 trees, dividing 80% training data and 20% testing data, the R2 performance score was 86%, the MSE score was 12%, the RMSE score was 35% and the MAE score was 22%. The 10-fold cross-validation score in this study was 85%. This shows that the Random Forest Regression method using 80% training data produces the best performance score.